The microbiome is dispensable for normal respiratory function and chemoreflexes in mice - Lusk, Savannah; Memos, Nicoletta K.; Rauschmayer, Andrea; Ray, Russell S. (Frontiers in Physiology, 2024)
Increasing evidence indicates an association between microbiome composition and respiratory homeostasis and disease, particularly disordered breathing, such as obstructive sleep apnea. Previous work showing respiratory disruption is limited by the methodology employed to disrupt, eliminate, or remove the microbiome by antibiotic depletion. Our work utilized germ-free mice born without a microbiome and described respiratory alterations. We used whole-body flow through barometric plethysmography to assay conscious and unrestrained C57BL/6J germ-free (GF, n = 24) and specific-pathogen-free (SPF, n = 28) adult mice (with an intact microbiome) in normoxic (21% O2,79% N2) conditions and during challenges in hypercapnic (5% CO2, 21% O2, 74% N2) and hypoxic (10% O2, 90% N2) environments. Following initial plethysmography analysis, we performed fecal transplants to test the ability of gut microbiome establishment to rescue any observed phenotypes. Data were comprehensively analyzed using our newly published respiratory analysis software, Breathe Easy, to identify alterations in respiratory parameters, including ventilatory frequency, tidal volume, ventilation, apnea frequency, and sigh frequency. We also considered possible metabolic changes by analyzing oxygen consumption, carbon dioxide production, and ventilatory equivalents of oxygen. We also assayed GF and SPF neonates in an autoresuscitation assay to understand the effects of the microbiome on cardiorespiratory stressors in early development. We found several differences in baseline and recovery cardiorespiratory parameters in the neonates and differences in body weight at both ages studied. However, there was no difference in the overall survival of the neonates, and in contrast to prior studies utilizing gut microbial depletion, we found no consequential respiratory alterations in GF versus SPF adult mice at baseline or following fecal transplant in any groups. Interestingly, we did see alterations in oxygen consumption in the GF adult mice, which suggests an altered metabolic demand. Results from this study suggest that microbiome alteration in mice may not play as large a role in respiratory outcomes when a less severe methodology to eliminate the microbiome is utilized.